PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR TINGKAT TINGGI PADA MATERI PENCEMARAN LINGKUNGAN KELAS X TSM 1 DI SMK PESANTREN CIWARINGIN - Kurniasih, Linda (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kuningan, 2023)
APPLICATION OF THE PROJECT BASED LEARNING LEARNING MODEL TO IMPROVE HIGH-LEVEL THINKING SKILLS ON CLASS X TSM 1 ENVIRONMENTAL POLLUTION MATERIAL AT SMK PESANTREN CIWARINGIN ABSTRACT This study aims to determine whether or not students' high-level thinking skills increase after carrying out learning using the Project Based Learning model, find out the presentation of students who get less and or more than the criteria for student achievement and know the presentation of students' answers at each cognitive level. The research method was carried out using quantitative methods on students of SMK Pesantren Ciwaringin class X TSM 1 on environmental pollution material. The results of the study showed that before carrying out the learning process of students who reached the criteria for student achievement only 7 students or only 23%, then the number of students who did not reach the criteria for student achievement was 23 students or 77%. Meanwhile, after carrying out learning, the number of students who reached the student achievement criteria increased to 20 students or reached 67%, then the number of students who did not reach the student achievement criteria decreased to 10 students or 33%. The results of the study based on questions at each cognitive level stated 62.5%-82% who answered the C4 cognitive level correctly and 37.5%-18% who answered incorrectly. 54%-76% answered the C5 cognitive level correctly and 46%-24% answered incorrectly. Then 10% - 33% who answered with a cognitive level of C6 correctly and 90% - 67% who answered incorrectly. From these data, it can be concluded that students of SMK Pesantren Ciwaringin class X TSM 1 have increased in high-level thinking skills, the difference between students who reach and have not reached the criteria for student achievement is only 34%, and the questions that students can answer are at the cognitive level C4-analyzing while the least answered by students is C6-creating. Keywords: High-level thinking, PJBL model,Learning results